The relationships between plasma substrates and hormones and the severity of injury in 277 recently injured patients. - Stoner, H; Frayn, K; Barton, R; Threlfall, C; Little, R (1979)
1. The plasma concentrations of glucose, lactate, amino acids, non-esterified fatty acids, glycerol, ketone bodies, ethanol, cortisol and insulin were measured in patients within a few hours of injury and before treatment. The severity of the injuries was assessed by the Injury Severity Score (ISS) method. 2. Plasma lactate and glucose concentrations both rose significantly with increasing ISS. 3. The concentrations of non-esterified fatty acids and glycerol were greater after moderate (ISS 7-12) than after minor (ISS 1-6) injuries. The glycerol concentrations were no higher and the non-esterified fatty acid concentrations were lower after severe (ISS > 12) than after moderate injuries. The concentrations of total ketone bodies tended to follow those of non-esterified fatty acids and there was a highly significant correlation between them. 4. The total concentration of amino acids was not affected by the severity of injury and there were no systematic changes in the concentrations of individual ones. 5. Plasma insulin concentrationsa were very variable and not related to severity. A weak correlation with the plasma glucose concentration seen after minor and moderate injuries was lost in the severely injured. 6. The plasma cortisol concentration was positively related to ISS up to ISS 12 but negatively so in the severely injured. 7. Factors such as age, sex and time after last meal were investigated. The most important factor modifying the response was intake of ethanol, which reduced the plasma concentrations of glucose, non-esterified fatty acids and alanine and raised that of lactate as well as the [β-hydroxybutyrate]/[acetoacetate] ratio.